2017
DOI: 10.1186/s40798-017-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Relative Age Effect and Lengths of Professional Careers in Male Japanese Baseball Players: a Retrospective Analysis

Abstract: BackgroundThe mechanisms underlying the relative age effect in sport events have been investigated for more than two decades. The present study focused on the relationship between the relative age effect and lengths of professional careers among professional male Japanese baseball players.MethodsThe birth dates of players and lengths of professional careers were collected from an official publication, and data were divided into four quarters (Q1: April–June; Q2: July–September; Q3: October–December; Q4: Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…This finding suggests that long-term disadvantages exist, even if physical maturity evens out between relatively older and younger players toward adulthood. Nakata [22] also reported that RAEs among NPB players were associated with the lengths of professional careers, indicating long-term effects after becoming professional players.…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that long-term disadvantages exist, even if physical maturity evens out between relatively older and younger players toward adulthood. Nakata [22] also reported that RAEs among NPB players were associated with the lengths of professional careers, indicating long-term effects after becoming professional players.…”
Section: Introductionmentioning
confidence: 99%
“…Within the same age category, there can be a difference of almost a full year between the oldest and youngest children. RAEs have been confirmed in many sports, including soccer [ 1 , 2 ], baseball [ 3 , 4 ], basketball [ 5 , 6 ], handball [ 7 ], swimming [ 8 , 9 ], track and field [ 10 , 11 ], sumo wrestling [ 11 ], rugby [ 12 ], and alpine ski racing [ 13 , 14 ]. The attributes of greater height, mass, aerobic power, muscular strength, endurance, and speed provide performance advantages in most sports, giving relatively older children advantages in sporting ability, psychological confidence, instruction, and playing time [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…RAEs have been confirmed in many sports, including soccer [1,2], baseball [3,4], basketball [5,6], handball [7], swimming [8,9], track and field [10,11], sumo wrestling [11], rugby [12], and alpine ski racing [13,14]. The attributes of greater height, mass, aerobic power, muscular strength, endurance, and speed provide performance advantages in most sports, giving relatively older children advantages in sporting ability, psychological confidence, instruction, and playing time [15] In addition to physiological and psychological factors, the competition principle has also been considered as an important factor affecting RAEs.…”
Section: Introductionmentioning
confidence: 99%